Unleashing the Country's Full Potential to Attract FDI - Mendoza, Ronald U (Archīum Ateneo, 2018)
With the existing trajectory path of the Philippines’ advancement aspirations, there is challenge that lies in sustaining and dramatically elevating the growth in foreign direct investments (FDI), which are critical for the country’s economic development. In light of the impending reforms that aim to fast track economic growth in the country, this paper provides an overview of the current economic landscape in view of foreign direct investments. We examined the prevailing political noises that dictate investment prospects and analyzed foreign direct investments across administrations and against its competition among neighbor countries. Tracking down foreign direct investments in the past 6 years from 2012 to 2017 shows that FDI since 2010 has exhibited an upward trend, but the “long game” in FDI is not built on quick spurts—it is more amply compared to a marathon underpinned by strong institutions and fundamentals. If we were to use a health analogy, the evidence presented suggests that ours is a generally healthy economy, posting impressive growth, but carrying some structural flaws. A successful cure will likely come at the hands of skilled and respected surgeons wielding scalpels, rather than those who would wield axes, doing more harm than good.